Análise molecular de estirpes de Escherichia coli enteropatogênica (EPEC) isoladas de animais e humanos - Beraldo, Lívia Gerbasi [UNESP] (2015)
Escherichia coli (EPEC) is a category of E. coli in interest in public health, as it is responsible for causing diarrhea, especially in children in developing countries. A total of 68 strains of EPEC isolated from humans and animals (buffalo, sheep and pigs) were analyzed for virulence markers, serotyping, subtyping of the eae gene and similarity clonal by electrophoresis in pulsed-field gel electrophoresis (PFGE). The PCR results showed that six human isolates had the bfp gene (typical EPEC), and 62 strains only had the eae gene (atypical EPEC). These strains belonged to 39 EPEC O: H serotypes including classical EPEC that are related to diseases in humans, such as O26: H11, O128: H2 and other serotypes that were related to people with diarrhea, as O8: H16 and O76:H7. Six types of intimin were detected among the 68 strains of EPEC, and 1, 2, 1, , and . The PFGE analysis, after XbaI digestion was performed on 68 strains of EPEC. The isolates were shown in heterogeneous PFGE and had 55 different profiles. Regarding the Phylogeny most strains of EPEC were classified into the group B1. Furthermore, some strains have been classified in group D, which consist of the E. coli strains that cause extra-intestinal infections. The presence of potentially pathogenic for humans types of EPEC and EPEC strains isolated from animals that may indicate disease transmission between animals and humans can occur and have an impact on public health. Furthermore, the role of these animals as EPEC carriers should be considered in outbreak investigations diarrhea. Keywords: EPEC, virulence genes, PFGE, zoonosis